Changing Approaches to Local History : Warwickshire history and its historians. - Dyer, Christopher (Boydell & Brewer, Inc., 2022)
Develops an understanding of Warwickshire's past for outsiders and those already engaged with the subject, and to explore questions which apply in other regions, including those outside the United Kingdom.